Asentamientos de Argopecten purpuratus, sobre vestigios de alga Rhodymenia sp., que resistió efectos del ENOS 97-98, en la Reserva Marina La Rinconada, Antofagasta, Chile (Revista de Biología Marina y Oceanografía, 2022)
The presence of Rhodymenia sp., under the thermocline after El Niño (ENSO) allowed massive settlements of two cohorts of Argopecten purpuratus in March 1999, reaching 1,152 ind. m-2, with size of 7.0 and 4.4 mm. In the mid of June, the spat moved towards shallow waters, with an average density of 19.1 ind. m-2, that was reduced to 14.0 ind. m-2 in March 2000 reaching two cohorts of 75.1 and 67.9 mm. It is concluded that algae that resist warming of ENSO would act as settlement zones for the pediveliger, diminishing the effect of wear in the post ENSO recruitment registered by A. purpuratus population in Chile.